Industry 4.0: Challenges and Opportunities in Competency Development for Defense Apparatus’ Human Resources - Eko Bambang Wibowo, Tri Legionosuko, Jonni Mahroza, Yudhy Chandra Jaya (International Journal of Advanced Science and Technology, 2020)
Industry 4.0 is an industrial revolution era that combines cyber technology and automation technology. In the future, manufacturing activities will be integrated through the massive use of wireless connection and big data. To prepare for this, stakeholders in defense need to develop strategic efforts so as not to be left behind and be disadvantaged by technological advancement. Anticipatory steps to face digital developments, mastery of defense technology, and competency development of defense apparatus' human resources are some of the efforts that can be made to face Industry 4.0. With a qualitative approach and descriptive analysis method, this study aims to analyze the opportunities that can and must be taken by stakeholders of defense to develop the competencies of their human resources. The study found that the euphoria for the emergence of information technology and information systems has taken place, which then becomes a new challenge for defense apparatus’ human resources. To develop the competency of human resources in defense, capacity building in the field of leadership is necessary. In addition, stakeholders also need to improve and manage the inputs (budget) to ensure optimal defense apparatus’ human resource capacity and competency.